Proteção e nutrição foliar na produção de massa seca, acúmulo, extração e exportação de macro e micronutrientes em híbridos de milho - Faria, Marcos Vieira de (2014)
Corn is a very important crop in Brazil and worldwide and, to increase dry matter production, and nutrient accumulation, extraction and exportation, a balanced nutrition and leaf protection should be done keeping them active up to the end of the crop cycle, in order to allow the processing of absorbed nutrients and photo-assimilates distribution. Thus, the purpose of this study was to evaluate the effect of leaf protection and nutrition over dry matter yield, macro and micronutrient accumulation, extraction and exportation on two corn hybrids. The experiment was installed in 2010/2011 crop season, at Iraí de Minas MG. The experimental design utilized was a DBC with eight replications, as a 2x2 factorial. Two experimental high potential corn hybrids were used, consisting of different genetic environments and two chemical environments (with or without leaf protection and nutrition). The genetic environment distinction was characterized by the resistance to leaf white spot complex, one was resistant while the other was susceptible. Plant leaf protection consisted of spraying ditiocarbanate and a commercial mixture of triazole with strobirulin, and nutrient leaf nutrition by the application of Co, Mo and Mn phosphite, on V8, VT and R2 stages. The use of leaf protection and nutrition increased dry matter in all parts of the susceptible plant: leaf, stalk, modified leaf, cob, plant body and dry kernel matter. Protection and leaf nutrition of the resistant hybrid increased dry leaf, stalk, modified leaf, cob and plant body matter, while no effect was observed for dry kernel and whole plant weight. With leaf nutrition and protection occurred an increase of N, P, K, Ca, Mg, Cu, Mn and Zn all over the plant. The average nutrient extraction was as followed in decreasing order, N (252,77 kg ha-1) > K (238, kg ha-1) > P (52,22 kg ha-1) > Ca (43,30 kg ha-1) > Mg (31,10 kg ha-1) > S (14,85 kg ha-1) > Fe (4.643,63 g ha-1) > Mn (500,74 g ha-1) > Zn (490,40 g ha-1) > Cu (116,42 g ha-1) > B (114,70 g ha-1) . The average nutrient exportation was as followed: N (164,79 kg ha-1, 65,20%) > K (83,18 kg ha-1, 34,89 %) > P (45,74 kg ha-1, 87,59 %) > Ca (19,78 kg ha-1, 45,68 %) > Mg (13,73 kg ha-1, 44,15%) > S (7,81 kg ha-1, 52,59%) > Fe ( 370,08 g ha-1, 7,97 %) > Zn ( 345,56 g ha-1, 70,53 %) > Mn (109,81 g ha-1, 21,93 %) > Cu ( 54,36 g ha-1, 46,69 %) > B ( 52,00 g ha-1, 45,34%). The nutrients required for a tone of grain production were: 20,67 kg of N; 4,27 kg of P; 19,50 kg of K; 3,54 kg of Ca; 2,54 kg of Mg; 1,21 kg of S; 9,38 g of B; 9,52 g of Cu; 379,80 g of Fe; 40,95 g of Mn and 40,10 g of Zn.